Sidoarjo Local Government Strategy in Handling Homelessness - Bahlamar, Ahmad Riyadh Umar (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to describe and analyze the strategy of the Social Service in overcoming the homeless and beggars in Sidoarjo Regency and to describe and analyze the constraints of the Social Service's strategy in overcoming the homeless and beggars in Sidoarjo Regency. This research is based on the fact that there are still many homeless people and beggars on the streets. This research method uses descriptive qualitative, data collection is done by conducting interviews, observation, and documentation. The technique of determining the informants used a purposive sampling technique. The technical analysis in this study is a qualitative analysis type that refers to the theory of Miles and Huberman. The results showed that the Strategy of the Social Service in Overcoming Homeless and Beggars in Sidoarjo Regency related to achieving the goals could be said to have not been fully successful, as evidenced by the large number of homeless and beggars roaming around, but regarding the provision of guidance after a raid by the Satpol PP, there were homeless and beggars who work and leave their previous activities. Meanwhile, the obstacles to the Social Service strategy in dealing with homeless people and beggars are the mindset that does not want to change for the homeless and beggars, a sense of laziness, and disobedience to the homeless and beggars when participating in the coaching program, and also from the people who still give them money to the community.